CORPORATE GOVERNANCE, PROFITABILITY AND DIVIDEND POLICY - Richard F. Simbolon (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2019)
Abstract: This study aims to determine the relationship of Corporate Governance and Profitability on Dividend Policy on pharmaceutical subsector companies listed on the Indonesia Stock Exchange in 2015-2017 either partially or simultaneously. The relationship will be used to identified…. The method used in this research is descriptive method, using ratio analysis of the proportion of the Board of Commissioners, Return On Equity, and Dividend Payout Ratio, descriptive analysis, significance test, correlation test, determination test, classic assumption test, linear regression analysis. The results showed that there was a significant influence between Good Corporate Governance and Dividend Policy which can be seen from the significant value of 0.016 <0.05 so that Ho is rejected and Ha is accepted, and there is a significant influence between Good Corporate Governance and Profitability on Dividend Policy with F count 4,834 significant level of 0.016 <0.05